ETOS KERJA TUTOR PROGRAM PENDIDIKAN KESETARAAN PAKET C DI PKBM INSAN CENDEKIA KELURAHAN SIALANG MUNGGU, KECAMATAN TAMPAN, KOTA PEKANBARU - Rahmat, Miki; Maemunaty, Titi; Ayub, Daeng (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The formulation of the problem in this research is how is the work ethic of the tutor for the package C equality education program at the Insan Cendekia Community Learning Center (PKBM) Sialang Munggu Village, Tampan District, Pekanbaru City? This study aims to determine how good the work ethic of the tutor for the package C equivalence education program at the Insan Cendekia Community Learning Center (PKBM) Sialang Munggu Village, Tampan District, Pekanbaru City. This study has 6 indicators (1) Likes to work hard, (2) Punctual, (3) Responsible, (4) Confidence, (5) Honest attitude and (6) Likes to work together. This research is descriptive with a qualitative approach. Qualitative descriptive research is used to examine the condition of natural objects. By using a qualitative approach, the purpose of this study is to find out and analyze how well the work ethic of tutors at the Pusat Kegiatan Belajar Masyarakat (PKBM) is located on Jl. Cipta Karya, Kelurahan Sialang Munggu, Kecamatan Tampan, Kota Pekanbaru. Based on the results of the study, it can be concluded that the work ethic of the Tutor of the Package C Equality Education Program at the Pusat Kegiatan Belajar Masyarakat (PKBM) Insan Cendekia, Sialang Munggu Village, Tampan District, Pekanbaru City is classified as very good, this can be seen from the tutors at PKBM. from the activities of tutors who can still manage time even though they work in two different places, tutors at PKBM Insan Cendekia are always on time in carrying out their work, tutors at PKBM Insan Cendekia are quite honest and admit that their competence is a little lacking but still try to develop their competencies and tutors those in PKBM Insan Cendekia are a little lacking in terms of cooperation. However, this is not due to an attitude of individualism, but because most of the tasks or work carried out are more independent.Key Words: Work Ethic, Tutor, Equality Package C, PKBM